The Use of Role-Playing to Enhance Management Students' Speaking Abilities in Business English Classes - Nurdiana, Nika; Rafikah, Syarifah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aimed to tackle the issue of learning Business English, particularly to enhance first-semester students' comprehension of role-playing at Wira Bhakti University. This research employed a quantitative approach, emphasizing the necessity for evaluative criteria in role-playing pedagogy. The intervention had two cycles, each consisting of two meetings, which included planning, execution, observation, assessment, reflection, and subsequent planning. The study's subjects were Wira Bhakti University first-semester Management A students. The results of the study indicated that the application of the role-playing learning model encouraged students to actively engage in classroom learning. The implementation of this model enhanced students' English-speaking skills by 20% and achieved a learning completion rate of 75%. In conclusion, the use of the role-playing learning model contributed to reducing students' speaking errors.